Effect of residual reagents on chalcopyrite losses at Mount Isa Mines copper Operation: Part II - evaluation of flotation mechanisms. (July 2022) - Forbes, Elizaveta; Brito e Abreu, Susana; Tungpalan, Kate; Sashigunan, Ramya; Runge, Kym; O'Donnell, Roxanne
Graphical abstract: Highlights: Part I of this works has demonstrated that decontaminating Mt Isa Mines process water improves chalcopyrite losses by circa 66%, attributed to the reduction in both the degree of entrainment and recovery by true flotation. The decrease in the degree of chalcopyrite entrainment can be attributed to the removal of residual MIBC from the process water. The reduction true flotation of chalcopyrite can be ascribed to partial removal of residual collector species, as well as the increased degree of chalcopyrite surface oxidation. Abstract: Mount Isa Mines Copper Operation (MICO) is one of the largest copper producers in Australia. The concentrator has a complex circuit, which includes a pre-flotation section designed for early removal of deleterious talc, and other naturally floating gangue including carbonaceous material. The downside of early talc removal is the loss of chalcopyrite to the pre-flotation concentrate. This work investigates the role of residual collector and frother reagents on chalcopyrite losses in the MIM pre-flotation circuit, and the possibility of improving talc recoveries whilst keeping chalcopyrite loss to a minimum. In Part I of this study, it was demonstrated that talc/chalcopyrite selectivity can be improved by removing residual reagents from the MIM process water. In Part II, the mechanisms of chalcopyrite losses are evaluated to explain the results presented in Part 1. This is done through an evaluation of mineral recoveries by true flotation and entrainment. The effect of residual reagents on chalcopyrite surfaces is evaluated using statistical analysis of Time-of-Flight Secondary Ion Mass Spectroscopy (ToF-SIMS) performed on process stream samples.